2013
DOI: 10.1017/s0967199413000166
|View full text |Cite
|
Sign up to set email alerts
|

Expression levels of mRNA for insulin-like growth factors 1 and 2, IGF receptors and IGF binding proteins in in vivo and in vitro grown bovine follicles

Abstract: This study investigated mRNA levels for insulin-like growth factors (IGFs) IGF1 (IGF-I) and IGF2 (IGF-II), IGF receptors (IGF1R and IGF2R), and binding proteins (IGFBP-1, IGFBP-2. IGFBP-3, IGFBP-4, IGFBP-5 and IGFBP-6) in bovine follicles of 0.2, 0.5 or 1.0 mm in diameter. mRNA expression levels in in vitro cultured follicles that reached approximately 0.5 mm were compared with that of in vivo grown follicles. IGF1R and IGF2R expression levels in 0.5 mm in vivo follicles were higher than in 1.0 or 0.2 mm folli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…IGF is involved in proliferation and follicular development, while IGFBP is responsible for the average lifespan of these ligands and their transport. Rebouc¸as et al (2014) detected IGF in bovine follicles with diameters of 0.2, 0.5 and 1.0 mm and found that the expression levels of IGF1R and IGF2R in 0.5 mm follicles were higher than those in 1.0 or 0.2 mm follicles. Furthermore, the mRNA expression levels of IGF were different in follicles of different sizes.…”
Section: Discussionmentioning
confidence: 97%
“…IGF is involved in proliferation and follicular development, while IGFBP is responsible for the average lifespan of these ligands and their transport. Rebouc¸as et al (2014) detected IGF in bovine follicles with diameters of 0.2, 0.5 and 1.0 mm and found that the expression levels of IGF1R and IGF2R in 0.5 mm follicles were higher than those in 1.0 or 0.2 mm follicles. Furthermore, the mRNA expression levels of IGF were different in follicles of different sizes.…”
Section: Discussionmentioning
confidence: 97%
“…The IGF-1 receptor mediates IGF-1’s biological effects. [ 22 ] IGF-1 induces ameloblast and odontoblast differentiation, increases dentin regeneration, and creates complex structures that resemble enamel and dentin. IGF-1 has been shown to promote dental pulp cell proliferation and mineralization.…”
Section: Discussionmentioning
confidence: 99%
“…IGF-1 has been shown to promote dental pulp cell proliferation and mineralization. [ 22 ] In addition, stem cells from the apical papilla and periodontal ligament that are odontogenic in nature can multiply and differentiate in response to IGF-1. [ 22 ] It has been hypothesized that IGF-1 may have an impact on hDPSC proliferation through ERK1/2 MAPK activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Insulin-like growth factor-1 (IGF-1) regulates many intraovarian activities (follicular growth, hormones selection, atresia, cell differentiation, steroidogenesis, and oocyte maturation) as a paracrine or endocrine factor during follicular development [ 3 ] and performs its biological function by binding to IGF binding proteins (IGFBPs) or IGF-1 receptor (IGF-1R) [ 4 ]. Previous research reported that Igf-1 was expressed in the ovaries of different species [ 5 , 6 ], and IGF-1 could improve oocyte maturation rate and quality in vitro [ 7 ]. Both male and female Igf-1 knockout mice were infertile, and the size of the ovaries of Igf-1 −/− female mice was less than half of the normal.…”
Section: Introductionmentioning
confidence: 99%